Upaya Meningkatkan Kemampuan Mengingat Kosakata Bahasa Arab Pada Anak Usia Dini Melalui Metode Gerak Dan Lagu - Nursyahadati, Zahra; Yulianingsih, Yuyun; Syam'iyah, Syam'iyah (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2023)
This study is driven by the issue of suboptimal retention of Arabic vocabulary among young children, thereby necessitating an effective and engaging technique. One promising approach is the integration of motion and song to facilitate learning material recall and bolster concentration through synchronous physical response to the musical stimuli. The aim of this research is to investigate the impact of the motion and song method on children's ability to remember Arabic vocabulary. A collaborative, classroom action research approach was utilised, with 16 children as participants. The aim of this research is to investigate the impact of the motion and song method on children's ability to remember Arabic vocabulary. The aim of this research is to investigate the impact of the motion and song method on children's ability to remember Arabic vocabulary. Prior to the implementation of the motion and song method, an initial analysis indicated that the average score for children's Arabic vocabulary recall was 37%. Specifically, during cycle I, the mean percentage value was 52%, whereas during cycle II, the average percentage value elevated to 76%. After implementing the motion and song method, a noteworthy enhancement in remembering Arabic vocabulary in early childhood occurred. Hence, it is established that the motion and song method can upgrade the recollection of Arabic vocabulary in early childhood.